Pengaruh Religiusitas, Dan Harga Terhadap Minat Beli Fashion Halal Dengan Sikap Sebagai Variabel Intervening Religiusitas (Studi Di Kota Kendari Provinsi Sulawesi Tenggara) - Rudi Kurniawan; La Ode Alimusa; Al Asy Ari Adnan Hakim (ITB AAS INDONESIA Surakarta, 2022)
This study aims to determine the effect of religiosity and price on interest in buying halal fashion through attitude variables as an intervening variable in Kendari City. The sample in this stud is 100 halal fashion consumers in Kendari City, obtained by purposive sampling. All data obtained through infrastructure deployment via GoogleForms are analyzed using Smart PLS. This study concludes that religiosity has a positive and significant effect on buying interest in halal fashion, the price has a positive and significant effect on attitudes, the price has a positive and significant effect on buying interest, and religiosity has a positive and significant effect on purchasing through attitude mediation. Thus, the price affects the low attitude and interest in buying halal fashion in Kendari City, while religiosity can affect the interest in buying halal fashion in Kendari City either directly or through attitude mediation.